Experimental Investigation of Shale Rock Properties Altering In-Situ Gas Density and Storage - Lou, Xuanqing; Chakraborty, Nirjhor; Karpyn, Zuleima (Frontiers in Earth Science, 2022)
Shale gas reservoir has become a crucial resource for the past decade to sustain growing energy needs while reducing the carbon intensity of energy systems relative to other fossil fuels. However, these reservoirs are geologically complex in their chemical composition and dominance of nano-scale pores, resulting in limited predictability of their effective storage capacity. To predict gas storage and estimate volumetric gas-in-place, in-situ gas properties need to be defined. However, only a few direct experimental measurements on in-situ gas properties are available in the literature, and the interactions between gas and the surrounding surface area of the medium remain poorly understood. In this study, gas invasion experiments were conducted in conjunction with 3D X-ray micro-CT imaging on three different shales, i.e., Bakken, Haynesville and Marcellus. Results show evidence of increased storage capacity in all cases, with different degrees of gas densification across the three shale specimens. The average of measured in-situ xenon density within the Bakken, Haynesville and Marcellus shale samples were found to be 171.53kg/m3, 326.05kg/m3 and 947kg/m3, respectively. These measured densities are higher than their corresponding theoretical free gas density, though lower than the xenon density at boiling point, indicating that current practices of estimating adsorbed gas and gas in place, using boiling point liquid density, may be overestimated. The xenon densification factor in the Marcellus sample was found to be 7.4, indicating the most significant degree of localized densification. This densification factor drops to 2.6, and to 1.4, in the Haynesville and the Bakken sample, respectively. Characterization of shale composition and pore structure are presented, in order to assess the shale properties controlling in-situ gas density and storage capacity. Results indicate that the observed degree of gas densification in shales can be attributed to surface area and pore size. The findings in this work provide valuable reference for simulation to much more accurately predict gas storage in shales. More importantly, the contribution of this work lay a foundation to evaluate excess storage capacity of various gases in ranging tight formations.